Starvation Promotes Autophagy-Associated Maturation of the Testis in the Giant Freshwater Prawn, Macrobrachium rosenbergii - Kankuan, Wilairat; Wanichanon, Chaitip; Morani, Federica; Thongrod, Sirorat; Titone, Rossella; Siangcham, Tanapan; Masini, Matilde; Novelli, Michela; Sobhon, Prasert; Isidoro, Ciro (Frontiers in Physiology, 2019)
Autophagy is a degradative process of cellular components accomplished through an autophagosomal-lysosomal pathway. It is an evolutionary conserved mechanism present in all eukaryotic cells and it plays a fundamental role in maintaining tissue homeostasis both in vertebrates and invertebrates. Autophagy accompanies tissue remodeling during organ differentiation. Several autophagy-related genes and proteins show significant upregulations following nutrient shortage (i.e., starvation). In our previous study we found that in female giant freshwater prawns subjected to a short period of starvation autophagy was up-regulated in consonant with ovarian maturation and oocyte differentiation. Whether and how starvation-induced autophagy impacts on testicular maturation and spermatogenesis of the male prawns remained to be investigated. In this study, we analysed the effects of starvation on histological and cellular changes in the testis of the giant freshwater prawn Macrobachium rosenbergii, that paralleled the induction of autophagy. Under short starvation condition, the male prawns showed increased gonado-somatic index, increased size and late stage of maturation of seminiferous tubules, which contained increased number of spermatozoa. Concurrently, the number of autophagy vacuoles and autophagy flux, as monitored by transmission electron microscopy and the autophagic marker LC3, increased in the testicular cells, indicating that a short period of starvation could induce testicular maturation and spermatogenesis in male M. rosenbergii along with modulation of autophagy.